2007
DOI: 10.1111/j.1462-5822.2007.01004.x
|View full text |Cite
|
Sign up to set email alerts
|

Type III secretion translocation pores of Yersinia enterocolitica trigger maturation and release of pro-inflammatory IL-1β

Abstract: Bacteria from the genus Yersinia deliver a number of effectors into host cells via type III secretion (T3S). Injected Yop effectors interfere and prevent pro-inflammatory warning signals by hijacking the host's intracellular machinery. While macrophages infected by wild-type Yersinia enterocolitica did not release mature IL-1beta, macrophages infected by Y. enterocolitica deprived of all effectors released mature IL-1beta. Surprisingly, macrophages infected by Y. enterocolitica deficient for secretion of all T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
50
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 73 publications
3
50
0
Order By: Relevance
“…It has been previously shown that Yop effectors inhibit expression and secretion of IL-1␤ in the macrophage-like cell line Mf4/4 infected with Y. enterocolitica (47,49). BMDMs were infected with different Y. pseudotuberculosis and Y. pestis strains to determine whether the T3SS and Yops of these species play a similar role in the inhibition of IL-1␤ release.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been previously shown that Yop effectors inhibit expression and secretion of IL-1␤ in the macrophage-like cell line Mf4/4 infected with Y. enterocolitica (47,49). BMDMs were infected with different Y. pseudotuberculosis and Y. pestis strains to determine whether the T3SS and Yops of these species play a similar role in the inhibition of IL-1␤ release.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have examined caspase-1 activation and IL-1␤ secretion in macrophages infected with Yersinia species (2,47,49). Schotte et al (47) examined these responses after they infected murine Mf4/4 macrophage-like cells with Y. enterocolitica E40 as well as different single or multiple yop mutants of this strain.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous mutant studies of Yersinia spp. revealed that it is the presence of the T3S translocon that triggers proinflammatory responses, which are in turn suppressed by translocated effector proteins (503). This predicted feedback regulation might itself be controlled by the degradation of effector proteins inside the host cell, as shown for YopE from Yersinia spp., which is degraded by the eukaryotic ubiquitination machinery.…”
Section: Port Of Entry For Effector Proteins-the Translocon and The Tmentioning
confidence: 92%